Software based signal generator and oscilloscope - Zaheed, Shaneela; Hossain, Mahfuz; Khan, Samiur Rahman (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.